Классификация объектов в режиме реального времени - Стахив, Ю. Н.; Заворотна, М. Г. (ХНУРЕ, 2019)
An important and urgent task in machine learning is the introduction and optimization of the technology for classifying objects in real time. For this project, completely local solutions were needed, for none of the existing ones in this area met the requirements of the planned one. Yolo - is an advanced object detection system in real time. It has a wide variety of configurations for any requirements. One of the tasks was the choice of configuration, which we will adapt to meet the objectives of the project. A suitable one was found among them, one that could work quickly even on smartphones or the Raspberry Pi - Tiny YOLO.
Keywords: класифікація об'єктів; YOLO; Raspberry Pi; система реального часу